2007
DOI: 10.1071/ar06148
|View full text |Cite
|
Sign up to set email alerts
|

Companion crop performance in the absence and presence of agronomic manipulation

Abstract: A field experiment located in southern New South Wales compared the component yields of cereal–lucerne companion crops (cereals sown into established lucerne) with the yields of cereal and lucerne monocultures. In-crop lucerne herbicide suppression, cereal crop types (wheat and barley), and top-dressed nitrogen (N) were evaluated for the potential to improve cereal production in the presence of lucerne. Plant populations and biomass, cereal grain yields, and grain quality (protein, screenings, and contaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…The LER values and incidence of overyielding (LER >1) was found to increase in seasons with more favorable growing‐season rainfall. This seasonal effect was also observed in an overcropping study that found a strong relationship between growing‐season rainfall and increased production of the companion crop (Harris et al, 2007). Cenpukdee and Fukai (1992) also reported that differences in growing‐season conditions affected competition of the two intercrop species.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The LER values and incidence of overyielding (LER >1) was found to increase in seasons with more favorable growing‐season rainfall. This seasonal effect was also observed in an overcropping study that found a strong relationship between growing‐season rainfall and increased production of the companion crop (Harris et al, 2007). Cenpukdee and Fukai (1992) also reported that differences in growing‐season conditions affected competition of the two intercrop species.…”
Section: Discussionsupporting
confidence: 63%
“…Overcropping cereals, the practice of seeding the crop directly into an established perennial pasture stand, is one means of overcoming the problem of lucerne removal (Davies and Peoples, 2003). Overcropping generally results in a yield reduction of the component species (Harris et al, 2007); however, overcropping productivity can be better than growing the sole components as separate stands or swards (Harris et al, 2007; Humphries et al, 2004). Additionally, overcropping is able to use more water than an annual system by exploiting the ability of the deep‐rooted perennial pasture species to recover water from deeper soil layers (Harris et al, 2008).…”
mentioning
confidence: 99%
“…Similarly, other research illustrated that cereal could improve legume yield by increasing Fe availability (Zuo et al, 2004). In short, crop management, including sowing time (Yu et al, 2016), row ratio (Surve and Arvadia, 2012), row spacing (Campiglia et al, 2014), and fertilization and sowing density (Pelzer et al, 2016), and climatic condition such as solar radiation, precipitation, and temperature (Harris et al, 2007;Brainard et al, 2011) are highly related to yield performances in intercropped systems. Strong competition for resources inevitably exists when wheat and faba bean are grown together due to similar growth duration and plant height; hence, higher productivity of wheat in intercropped systems may result in yield reduction of faba bean.…”
Section: Effects Of Cereal and Legume Intercropping On Crop Productionmentioning
confidence: 97%
“…A similar result was found in this study (i.e., wheat yield increased when wheat was intercropped with faba bean, but intercropping decreased faba bean yield; Table 1). In short, crop management, including sowing time (Yu et al, 2016), row ratio (Surve and Arvadia, 2012), row spacing (Campiglia et al, 2014), and fertilization and sowing density (Pelzer et al, 2016), and climatic condition such as solar radiation, precipitation, and temperature (Harris et al, 2007;Brainard et al, 2011) are highly related to yield performances in intercropped systems. Similarly, other research illustrated that cereal could improve legume yield by increasing Fe availability (Zuo et al, 2004).…”
Section: Effects Of Cereal and Legume Intercropping On Crop Productionmentioning
confidence: 99%
“…Intercropping of lucerne (Medicago sativa L.) and wheat (Harris et al 2008), and of summer-active perennial native grasses and wheat (Millar and Badgery 2009) have both received renewed interest and, although feasible, crop yields are nearly always subject to competitive interference (with the possible exception of yields in wet seasons) (Harris et al 2007a;2007b). Henry et al (2010) have examined the impact of 'intercropping' different lines of the same species (i.e.…”
Section: Intercropping and Phase Farmingmentioning
confidence: 99%